An experimental comparison of object-orientation and functional-decomposition as paradigms for communicating system functionality to users - Moynihan, Tony (The Journal of systems and software, 1996)
This article describes an experiment to evaluate the relative effectiveness of functional-decomposition and object-orientation as paradigms for client/developer communication in the early stages of the system development process. The subjects were 20 executives attending a management development program. The experimental task required the subjects to comment critically on the content and format of two analyses of equivalent content. The first analysis took the form of a functional-decomposition. The second analysis took the form of an object-model. The results suggest that functional-decomposition is the more effective of the two paradigms as a vehicle for early client/developer communication. Also, the subjects judged the functional-decomposition to be superior to the object-model on a number of important attributes.